Molecular testing for somatic mutations in common cancers: the views of UK oncologists. Issue 6 (27th May 2008) - Wordsworth, S; Buchanan, J; Papanicolas, I; Taylor, J; Frayling, I; Tomlinson, I
Abstract : Background: Somatic mutations are important determinants of cancer behaviour and response to therapy. However, molecular testing in this context has a relatively low profile within the clinical community, despite publicity surrounding targeted therapies such as Herceptin. Aims: As the testing process affects many stakeholders, especially oncologists, this paper examines current test request patterns and views of such testing. Methods: A postal questionnaire was mailed to 582 UK oncologists and haematologists, achieving a 20% response rate. Results: The survey revealed that immunohistochemistry and fluorescent in situ hybridisation are the most commonly requested tests (used by 70% and 55% of respondents, respectively), especially for breast cancer. Availability of suitable treatment options is the main factor influencing the decision to test (selected by 62% of respondents). Respondents were generally positive about future demand for immunohistochemistry, fluorescent in situ hybridisation, microarray analysis and DNA-based tests, but uncertain about the prospects for microsatellite instability and ploidy testing. Conclusions: Overall, respondents thought that somatic mutation testing could have a significant and positive effect on oncology and haematology departments and patient care, especially with better treatment and tumour classification. However, lack of supportive scientific evidence and funding were considered key barriers to widespread testing. Further research is clearly required on both the resource implications of this increase in demand and the best model of service delivery to ensure the most efficient use of health service resources.